Answer:
Both the zoo-keepers are correct.
Step-by-step explanation:
The first zoo keeper uses the equation:
x - 41.5 = 13.5
⇒ x = 13.5 + 14. 5 = 55
Now, the second zoo- keeper uses the equation:
41.5 + 13.5 = x
⇒ x = 55
Both use x = 55.
Just like that? Any question, inbox. :p
Answer:
1.5 + 0.5h = 5 and 0.5h + 1.5 + 5
Step-by-step
I think this would be the answer, sorry if it's not
Answer: -7y+8x
Step-by-step explanation: I assume you mean to simplify
Step 1: Remove parentheses : -4y - x - (3y - 9x)
Step 2: -(3y - 9x) = -3y + 9x
Step 3: Simplify: -4y - x - 3y +9x
Step 4: Answer: -7y+8x